Evaluation of soil flame disinfestation (SFD) for controlling weeds, nematodes and fungi - Xiao-ning WANG; Ao-cheng CAO; Dong-dong YAN; Qian WANG; Bin HUANG; Jia-hong ZHU; Qiu-xia WANG; Yuan LI; Can-bin OUYANG; Mei-xia GUO; Qian WANG (Journal of Integrative Agriculture, 2020)
Soil flame disinfestation (SFD) is a form of physical disinfestation that can be used both in greenhouses and on field crops. Its use for soil disinfestation in different crop growing conditions makes it increasingly attractive for controlling soil-borne pathogens and weeds. But little is known about the effect on weeds and soilbrone diseases. This study reports on greenhouses and field crops in China that determined the efficacy of SFD to control weeds, nematodes and fungi. It also determined the impact of SFD on the soil physical and chemical properties (water content, bulk density, NO3−-N content, NH4+-N content, conductivity and organic matter) in three field trials. A second generation SFD machine was used in these trials. SFD treatment significantly reduced weeds (>87.8%) and root-knot nematodes (Meloidogyne incognita) (>98.1%). Plant height and crop yield was significantly increased with SFD treatment. NO3−-N and NH4+-N increased after the SFD treatment, and there was also an increase in soil conductivity. Water content, bulk density and organic matter decreased significantly in the soil after the SFD treatment compared to the control. Soil flame disinfestation is a potential technique for controlling weeds and diseases in greenhouses or in fields. SFD is a non-chemical, safe, environmentally-friendly soil disinfection method.